التحليل الطاقي لدارة تبريد ثنائية المرحلة في معمل ألبان دمشق - عامر, عاطف (Latakia University Journal -Engineering Sciences Series, 2014)
إن الهدف من هذا البحث هو إجراء دراسة لواقع عمل محطة تبريد ثنائية المرحلة في معمل ألبان دمشق، و ذلك من أجل تحديد الضياعات لكل عنصر من عناصر هذه المحطة بحيث يمكن تلافي هذه الضياعات ورفع معامل أداء دارة التبريد، والتقليل من المصاريف الطاقية، و الوصول إلى نظام العمل التصميمي الأمثل . تم وضع طريقة لحساب معامل أداء الدارة وضياع الاكسرجي وكذلك وضع برنامج حاسوبي. وتمت مقارنة نتائج الحساب اليدوي بالبرمجيات الموضوعة. فكانت نتائج الحساب اليدوي متطابقة مع نتائج البرنامج و توصلنا إلى أنه أكبر نسبة ضياع في الاكسرجي هي في الضاغط ثم في المبخر و اخيراً في المكثف التبخيري. تم اقتراح حلول عملية من أجل تخفيض نسبة هذه الضياعات. The main objective of this paper is to analyze the energy performance of a two-stage refrigeration system at Dairy Factory at Damascus and define the losses in each element of the station in order to pinpoint the most energy inefficient part. We have worked on eliminating the losses and increased the Coefficient of Performance (COP) of the two-stage cycle and reduced the energy consumption in the system. We have put together a method to compute the COP and Exergy and compare the results with a home-made program based on the previous method. We have concluded that the compressor was the most energy consuming device, evaporator second and condenser third. We have recommended practical solutions for the losses in the system.